1997
DOI: 10.1128/jb.179.10.3354-3357.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and insertional inactivation of Streptomyces argillaceus genes involved in the earliest steps of biosynthesis of the sugar moieties of the antitumor polyketide mithramycin

Abstract: Two genes (mtmD and mtmE) were cloned and sequenced from the mithramycin producer Streptomyces argillaceus. Comparison with proteins in databases and enzymatic assays after expression in Escherichia coli showed that they encode a glucose-1-phosphate:TTP thymidylyl transferase and a TDP-D-glucose 4,6-dehydratase, respectively. The mtmD gene was inactivated by gene replacement, generating a nonproducing mutant that accumulates a tetracyclic compound designated premithramycinone. The identification of premithramy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
82
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 20 publications
0
82
0
Order By: Relevance
“…SuperCos-1 was purchased from Stratagene. pBSKT, an integrative vector carrying carbenicillin and thiostrepton resistances, was described by Lombo et al (1997). Carbenicillin (50 µg ml − ") and thiostrepton (50 µg ml − ") were used in the medium for selection of recombinant plasmids and strains.…”
Section: Methodsmentioning
confidence: 99%
“…SuperCos-1 was purchased from Stratagene. pBSKT, an integrative vector carrying carbenicillin and thiostrepton resistances, was described by Lombo et al (1997). Carbenicillin (50 µg ml − ") and thiostrepton (50 µg ml − ") were used in the medium for selection of recombinant plasmids and strains.…”
Section: Methodsmentioning
confidence: 99%
“…A 2.1-kb EcoRI fragment from cosmid 9-6G, which comprises part of the novT gene, was cloned into the EcoRI site of vector pBSKT, a pBluescript SK(ϩ) derivative containing the thiostrepton resistance gene (36), resulting in pAM1. Restriction analysis showed that the novT gene fragment had the same orientation as the thiostrepton and the ampicillin resistance genes of the vector.…”
Section: Novobiocin Is Produced By Streptomyces Spheroides Andmentioning
confidence: 99%
“…Mithramycin has been clinically used for the treatment of certain tumors, such as disseminated embryonic cell carcinoma, as well as for Paget's bone disease (12) and is also used for control of hypercalcemia in patients with malignant disease (1). The biosynthetic gene cluster for mithramycin has been fully characterized (2)(3)(4)(5)(6)9), and it has been found that although mithramycin is a tricyclic aromatic polyketide, its biosynthesis proceeds through tetracyclic intermediates. Many of these intermediates have been isolated from mutants blocked at different steps in the biosynthesis (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…The biosynthetic gene cluster for mithramycin has been fully characterized (2)(3)(4)(5)(6)9), and it has been found that although mithramycin is a tricyclic aromatic polyketide, its biosynthesis proceeds through tetracyclic intermediates. Many of these intermediates have been isolated from mutants blocked at different steps in the biosynthesis (2)(3)(4)(5)(6). Insertional inactivation of one of the genes of the mithramycin cluster, mtmOIV, generated a non-mithramycinproducing mutant that accumulated a fully glycosylated tetracyclic intermediate, premithramycin B (6).…”
mentioning
confidence: 99%